Analyzing the Global Visibility and Influence of Social Enterprise Research: A Bibliometric Review of Citation, International Collaboration, and Cross-Cultural Perspectives - Eri Mardiani; Waqiah; Siska Jeanete Saununu; Benny Novico Zani (Westscience Press, 2023)
The literature review highlights the growing research on social enterprises, exploring key concepts such as double bottom line and social impact assessment. While there has been progress, there are still gaps in understanding the global visibility and influence of social enterprise research. This research method fills the gap by using bibliometric analysis as a quantitative research method. The methodology section presents a comprehensive approach to data collection, extraction, and analysis. Relevant databases and sources are identified, and inclusion/exclusion criteria for publication are established. Keywords and search strategies are used to collect data on authorship, year of publication, journal, and number of citations. Bibliometric analysis techniques, including citation analysis and network analysis, are used to analyze data and uncover patterns and trends. The results and discussion sections present the findings of the bibliometric analysis. Citation patterns, influential works, and authors are identified, thus providing insight into the intellectual structure of the field. International collaboration trends and cross-cultural perspectives are analysed, highlighting global research networks and the application of social enterprise concepts across multiple contexts.